Fatigue failure mechanism analysis of 1Cr17Ni2 stainless steel blades ground by an abrasive belt - Zhang, Mei; Li, Long; Wang, Dongzhu; Yang, Xinshun (Frontiers in Materials, 2023)
Fatigue failure, as the main failure form of aero-engine blades, has a direct impact on the reliability and service life of aviation equipment. In order to improve the service performance of machined blades, it is necessary to understand the failure process and failure mechanism of blades, and then optimize the grinding process. This paper takes abrasive belt grinding of 1Cr17Ni2 stainless steel blade as the research object, and analyzes the fatigue failure mechanism by characterizing the surface morphology, cross-sectional micro-structure and cross-sectional characteristics of the fatigue failure blade. The results show that cracks are prone to propagate in carbon-rich areas with poor mechanical properties inside the material, and the accumulation of large-size carbon-rich areas is easy to form continuous cracks and accelerate crack growth. The grinding process promotes the migration and consumption of surface carbon elements, and forms a carbon consumption layer on the surface of the material, which can inhibit the initiation of fatigue cracks. The point-like pits on the ground surface have an adverse effect on the fatigue life and play a role in the initiation of fatigue cracks. enhancement. The direction of material research and development to homogenize the structure of the material and the direction of anti-fatigue grinding to increase the thickness of the carbon consumption layer on the ground surface and avoid the damage of micro-pits are proposed. The research has important guiding significance for anti-fatigue machining of key components.